Model Parenting keluarga Sakinah dalam Penguatan Karakter Generasi Alpha di Era Digital - Firman Robiansyah; Aulia Wulandari; Aulia Juliyanti; Syifa Maulidah (Universitas Negeri Medan, 2026)
This study aims to analyze the integration of Islamic values in family education as a strategy for character building among Generation Alpha in the digital era. Using a library research method with content analysis of relevant literature, the study finds that the formation of an Islamic family begins with spouse selection, marriage contract implementation, and continuous family development based on the principles of sakinah, mawaddah, and rahmah. Parents play a dominant role as primary communicators in internalizing the values of tauhid (monotheism) and noble character through verbal and non-verbal messages, exemplary behavior, supervision of technology use, and the implementation of healthy digital literacy and regulation at home. The synergy between Islamic education, Islamic parenting, and wise use of technology becomes a key strategy in shaping Generation Alpha to be morally grounded, resilient, and adaptive to contemporary challenges.